Novel Synthetic Antagonists of Canonical Wnt Signaling Inhibit Colorectal Cancer Cell Growth - Jo Waaler; Ondřej Machoň; Jens Peter von Kries; Steven Ray Wilson; Elsa Lundenes; Doris Wedlich; Dietmar Gradl; Jan Erik Paulsen; Olga Machoňová; Jennifer L. Dembinski; Huyen Dinh; Stefan Krauß (2011)
Abstract Canonical Wnt signaling is deregulated in several types of human cancer where it plays a central role in tumor cell growth and progression. Here we report the identification of 2 new small molecules that specifically inhibit canonical Wnt pathway at the level of the destruction complex. Specificity was verified in various cellular reporter systems, a Xenopus double-axis formation assay and a gene expression profile analysis. In human colorectal cancer (CRC) cells, the new compounds JW67 and JW74 rapidly reduced active β-catenin with a subsequent downregulation of Wnt target genes, including AXIN2, SP5, and NKD1. Notably, AXIN2 protein levels were strongly increased after compound exposure. Long-term treatment with JW74 inhibited the growth of tumor cells in both a mouse xenograft model of CRC and in ApcMin mice (multiple intestinal neoplasia, Min). Our findings rationalize further preclinical and clinical evaluation of these new compounds as novel modalities for cancer treatment. Cancer Res; 71(1); 197–205. ©2010 AACR.